Rectifying behavior of the GaAs / Er-doped SnO2 heterostructure: Interface dipole role and monochromatic light influence - Russo, Fabricio T. [UNESP]; Scalvi, Luis V.A. [UNESP] (Elsevier, 2024)
The characteristic current-voltage (I x V) curves are measured across the interface of a GaAs/SnO2 heterostructure, where the top layer (tin dioxide) is doped with 1 at% of the rare-earth Er. It leads to a diode-like behavior, which is associated with the presence of electric dipoles mainly at interface. Thermally stimulated depolarization current (TSDC) technique is also applied to this heterostructure in the dark and in the presence of monochromatic light from a He–Cd laser or a InGaN LED. The effect of monochromatic light on the possible formation or destruction of dipoles in this heterostructure system is analyzed by the I x V curves as well as by the TSDC data, considering the main types of defects in this structure: EL2 in the GaAs side, or oxygen vacancies and ionized Er ions in the SnO2 side. Photo-induced TSDC (PTSDC) points to the destruction of bands previously obtained in the dark, suggesting a large difference on the thermal and optical activation energies of defects. This effect is stronger with the illumination of a InGaN LED (2.76 eV) compared to He–Cd laser (3.80 eV) irradiation.
Keywords: Dipoles; Gallium arsenide; Heterostructure; Thin films; Tin dioxide